POTENSI ANTIOKSIDAN DAN ANTI-ELASTASE EKSTRAK DAUN KELOR (MORINGA OLEIFERA) TERHADAP ANTIAGING - Glorio ias Natanael; Gidion Franklin Simorangkir; Nanda Parariski Purba; Mardiana Putri br. Tambunan; Ali Napiah Nasution; Adek Amansyah (Universitas Prima Indonesia, 2021)
Skin aging caused by oxidative stress that leads to the formation of wrinkles, pigmentation, and asteatosis. On the other hand, the elastase enzyme also can influence the elasticity of the skin that leads to sagging. Moringa leaves (Moringa oleifera Lamk) has been reported contain some active compounds like flavonoid that has antioxidant and anti-aging potential. This study was presented to determine the potential of moringa leaves extract (MLE) in scavenging DPPH radicals and inhibiting the elastase enzyme. MLE was obtained by using maceration methods. The potential of MLE in scavenging DPPH radicals and inhibiting elastase enzyme was determined using spectrophotometric methods. MLE has IC50 value of DPPH scavenging activity also elastase inhibitory activity at 109.67 + 0.83 µg/mL and 159.67 + 7.95 µg/mL. MLE has antioxidant and anti-aging potential as indicated by DPPH scavenging activity and elastase inhibitory. However, MLE has moderate DPPH scavenging activity and low elastase inhibitory activity.